Computational Investigation of Growth Hormone Receptor Trp169Arg Heterozygous Mutation in a Child With Short Stature. Issue 12 (9th June 2017) - Porto, William Farias; Marques, Felipe Albuquerque; Pogue, Huri Brito; de Oliveira Cardoso, Maria Teresinha; do Vale, Maria Gabriela Rodrigues; da Silva Pires, Állan; Franco, Octavio Luiz; de Alencar, Sérgio Amorim; Pogue, Robert
ABSTRACT: Mutations in the growth hormone receptor ( GHR ) gene can cause disruption of the growth hormone signaling pathway, resulting in growth deficiency due to growth hormone (GH) resistance. Both recessive and apparently dominant mutations have been described in the literature. In order to shed some light on the molecular mechanism of partial growth hormone resistance caused by heterozygous mutations, we performed an in‐depth in silico analysis of a mutation found in a girl with a previous diagnosis of idiopathic short stature. An array of algorithms was used to predict pathogenicity and potential impact on the protein, and molecular modeling, docking and dynamics were used to determine structural consequences. The results suggest that both of the possible single mutation‐containing heteromeric GH–GHR complexes, as well as the double GHR mutant complex result in perturbation of complex structures, with altered ability of the GHR dimers to interact with the GH peptide. J. Cell. Biochem. 118: 4762–4771, 2017. © 2017 Wiley Periodicals, Inc. Abstract : In silico molecular dynamic analyses were used to investigate the molecular impact of a mutation in the growth hormone receptor protein. Data indicate that both heteromeric forms of the receptor have reduced capacity to react with growth hormone due to the presence of the mutation.